Development of Wordwall Educational Game-Based Learning Media for Social Studies Learning Materials - Harirah; Khairi, Ahmad Imam (IAIN Madura, 2025)
Learning media plays a crucial role in enhancing student interest, understanding, and engagement in the learning process. At SMP Negeri 1 Pamekasan, social studies learning is still dominated by conventional media, leading to student boredom, particularly among Generation Z and Alpha, who are more accustomed to technology. This study aims to develop and evaluate the validity of Wordwall educational games in social studies learning at SMP Negeri 1 Pamekasan. The research employs the Research and Development (R&D) method with the 4D development model by Thiagarajan, consisting of four stages: Define, Design, Develop, and Disseminate. Data collection was conducted using observation, interviews, questionnaires, and research instruments. Qualitative data analysis follows the Miles and Huberman framework, while quantitative data were processed to determine product feasibility using Eko Putro Widoyo's theory. The results indicate that the development of Wordwall-based educational game media for social studies subjects at SMP Negeri 1 Pamekasan, following the 4D model, is feasible, with a media feasibility score of 4.4 and a material feasibility score of 4.81, both categorized as